Learning to live together : preventing hatred and violence in child and adolescent development - Hamburg, David A., 1925-2019; Hamburg, Beatrix A. (Oxford University Press, 2004)
This title explores the psychological obstacles to peaceful relations between groups and focuses on the developmental processes by which we can diminish ethnocentrism, prejudice, and hatred, which children learn from a very early age.